Manajemen Keuangan dan Kesehatan Mental untuk Pekerja dan Mahasiswa Migran di Taiwan - Fatmasari Sukesti; Edy Purwanto; Muhamad Diaz Faturachman; M. Fatkhul Mubin; Desi Ariyana Rahayu (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
The community service aims to provide literacy on financial management and mental health for workers and students abroad. The education focuses on how migrants and students can manage their finances healthily while abroad and maintain their mental health during their time working or studying in Taiwan. The expected outcome is that participants gain additional knowledge on how to manage their finances and health while in a foreign country. With this knowledge, it is hoped that they can prevent mental health and financial issues, thus enabling them to work and study effectively and increase productivity.